ETNOGRAPHY OF COMMUNICATION OF ANIMAL LOVERS COMMUNITY JAKARTA - Lusyana; Imam Nuraryo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
This research examines ethnography of communication in Jakarta Dog Lovers can be divided into three main problems: first is a form of communication activities undertaken in the community, second is the communication components that make up the communication activities, and third is the communication competencies of community members while performing a communication activity. This study was studied by looking at the theory and method of ethnography of communication from Dell Hymes. The method of communication ethnography is one of the study of communication ethnography of some qualitative researchstudies (interpretive or constructivistparadigm),which is found in the discovery of various communication patterns used by humans in a speech society. The data collection techniques utilized is through the method of introspection, in-depth interviews, participant observation, and document analysis. The techniques of data analysisin this study uses the gradual advancement of 12-step flow analysisresearch approach created by James P. Spradley. The results of this research are divided into three main points based on the research objectives. First is the form of the communication activities in the community of Jakarta Dog Lovers as seen on the public gathering conducted routinely every weekend, charities, active participation on campaign events, as well as providing education to inform the general members of the public about the issues surrounding dogs. Second, there are ten components that make up the concept of communication activities. Third, the competencies of the members when interacting with fellow peers of their community. This research concludes that the communication activities conducted by the general public of the community is supported by the presence of communication elements and competencies of the members in interacting with one another in Jakarta Dog Lovers Community. This context is evidence of ethnography or cultural cultivation that occurs in Jakarta Dog Lovers. Researchers also suggest that research on Jakarta dog lovers community topics will be more developed in the future. Key words: Ethnography of Communication,Community, Jakarta Dog Lovers